2023
DOI: 10.3390/biomedicines11041014
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Damage, Inflammation and Microbiota Alteration during COVID-19 Infection

Abstract: Background: The virus SARS-CoV-2 is responsible for respiratory disorders due to the fact that it mainly infects the respiratory tract using the Angiotensin-converting enzyme 2 (ACE2) receptors. ACE2 receptors are also highly expressed on intestinal cells, representing an important site of entry for the virus in the gut. Literature studies underlined that the virus infects and replicates in the gut epithelial cells, causing gastrointestinal symptoms such as diarrhea, abdominal pain, nausea/vomiting and anorexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…The cause of gastrointestinal reaction caused by SARS‐CoV‐2 virus may be related to angiotensin‐converting enzyme 2 (ACE2) receptor binding. ACE2 receptors are highly expressed in intestinal cells (e.g., small intestine epithelial cells and large intestine epithelial cells) and are the main route by which viruses enter the intestine 47 . In addition, severe COVID‐19 patients often have gastrointestinal complications such as ileus, gastrointestinal bleeding, intestinal ischemia, and even intestinal perforation 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of gastrointestinal reaction caused by SARS‐CoV‐2 virus may be related to angiotensin‐converting enzyme 2 (ACE2) receptor binding. ACE2 receptors are highly expressed in intestinal cells (e.g., small intestine epithelial cells and large intestine epithelial cells) and are the main route by which viruses enter the intestine 47 . In addition, severe COVID‐19 patients often have gastrointestinal complications such as ileus, gastrointestinal bleeding, intestinal ischemia, and even intestinal perforation 48 .…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 receptors are highly expressed in intestinal cells (e.g., small intestine epithelial cells and large intestine epithelial cells) and are the main route by which viruses enter the intestine. 47 In addition, severe COVID‐19 patients often have gastrointestinal complications such as ileus, gastrointestinal bleeding, intestinal ischemia, and even intestinal perforation. 48 Fecal calprotectin is often considered to be an indicator associated with intestinal inflammation, and its most important use is in the differential diagnosis of inflammatory bowel diseases (IBD) and irritable bowel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive patient history must be obtained to rule out other conditions such as appendicitis, cholecystitis, colonic diverticulitis, pancreatitis, bowel obstruction, or foreign body perforation [3,4,[8][9][10][11][12][13][14][15][16][17][18][19][20]24,34]. An abdominal X-ray can help detect perforation or obstruction but cannot establish a diagnosis on its own.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous symptoms may accompany the severity of the disease. 77 The imbalance in gut microbiota may also be related to the imbalance in metabolite level, while the resulting inflammatory cytokine storm can cause overall immune disorders in the body. Viruses can easily invade the intestinal tract because of the high ACE2 expression in lung tissue and intestinal epithelial cells.…”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%
“…Disorder of intestinal flora destroys the gut–blood barrier and triggers immune activation, which is associated with systemic symptoms. 77 Multiomics association analysis revealed a potential regulatory relationship between intestinal flora and metabolites such as branched‐chain amino acids and the chemotactic response of inflammatory factors in patients with COVID‐19, and the intestinal flora may regulate lung and brain functions through metabolites. The severity of COVID‐19 is partly associated with host immune dysregulation, and Mendelian randomization studies have suggested that the gut microbiota is associated with susceptibility, hospitalization rate, and severity.…”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%